The Role of Parents on Student’s Interest in Futsal Extracurricular at SMA Negeri 1 OKU - Antariningsih, Ning; Manullang, Jujur Gunawan; Hermansah, Bambang (Yayasan Sembilan Pemuda Indonesia, 2023)
The purpose of this study was to evaluate the role of parents on students’ interest in futsal extracurricular at SMA N 1 OKU. This study was conducted on futsal extracurricular students at SMA N 1 OKU. This type of research is descriptive research. The method carried out in this study is a qualitative method with the use of observation methods and questionnaires. The study sample amounted to 30 people. Data collection techniques in this study using questionnaires, questionnaires are data collection techniques carried out by giving a set of questions or written questions to respondents to answer. The results of the analysis were influenced by factors within themselves as much as 54.87%, while the results of the analysis were influenced by factors from outside themselves as much as 50.6%. From the results of the analysis and data from the research that has been studied and the discussion that has been described on the previous page, the researcher can draw a conclusion that the role of parents on students’ interest and motivation in participating in extracurricular futsal at SMAN 1 OKU is influenced by internal influence factors and influences from outside where influence factors from within is more dominant than external influence factors.